Friction and wear behavior of TiN films against ceramic and steel balls. (August 2018) - Yan, Zhen; Jiang, Dong; Gao, Xiaoming; Hu, Ming; Wang, Desheng; Fu, Yanlong; Sun, Jiayi; Feng, Dapeng; Weng, Lijun
Abstract: Tribological properties and wear mechanisms of TiN films deposited by arc ion plating (AIP) against Si3 N4, Al2 O3 and steel balls were comparatively investigated under different loads and speeds. The tribological properties of the TiN films were evidently influenced by load, speed and counterball. The different friction coefficients were related to the real contact state of the friction interface of the tribopair. The TiN films against the ceramic balls mainly were typical polishing wear, which resulted from the interaction between the preferential formation of the Ti oxide layer on the wear track surface and the small particles from ceramic balls. For steel ball, the platelets of Fe3 O4 adhered to the wear track surface did not generate polishing effect. Highlights: Polishing wear occurred when the TiN films slid against ceramic balls. Polishing mechanism was correlated with Ti oxide layer and ceramic particles. Wear mainly resulted from adhesion and abrasion for the TiN film against steel ball.